Parsonage-Turner recurrent acute idiopatic neuralgic amyotrophy case. Case report - Elena A. Kovrazhkina; Tatiana A. Abramova; Anna V. Serdyuk; Vladimir G. Lelyuk (ZAO "Consilium Medicum", 2021)
Recurrent ParsonageTurner syndrome is a hereditary form of a syndrome from neuralgic amyotrophic group, with a characteristic clinical picture in the form of severe pain syndrome with remission and subsequent development of upper shoulder girdle atrophy, proceeding with the accumulation of neurological deficit. Despite the characteristic clinical picture, the syndrome requires a differential diagnosis with a number of conditions, in which electroneuromyography helps along with other techniques. Wherein neuropathic sings of the upper extremity nerves are usually detected, and the long thoracic and suprascapular nerves are most often affected, at that more often by axonopathic type. Electromyography reveals denervation sings in the upper brachial muscles. This article describes ParsonageTurner recurrent acute neuralgic amyotrophy case, discusses the issues of the clinical picture, diagnosis and treatment of this disease.